1968
DOI: 10.1073/pnas.61.2.693
|View full text |Cite
|
Sign up to set email alerts
|

On the recognition of serine transfer RNA's specific for unrelated codons by the same seryl-transfer RNA synthetase.

Abstract: The translation of a sequence of codons (in messenger RNA) into an amino acid sequence (in protein) is mediated by various species of aminoacyl-tRNA's.-1 2 There is evidence for the view that each transfer RNA species has a specific region whose nucleotide sequence is complementary to those of the codons specifying the aminoacyl residue attached to the transfer RNA. This region is designated as the anticodon.2-4 Unambiguous translation depends on correct matching of the anticodons in aminoacyl-tRNA's to codons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

1969
1969
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(13 citation statements)
references
References 9 publications
2
11
0
Order By: Relevance
“…Small differences in interaction of the mutant enzyme with the various isoacceptors would have gone undetected, but there seems to be no discrimination against a particular tRNA species by the mutant enzyme. The finding of the LeuRS and SerRS mutants provides genetic evidence for the existence of a single LeuRS and SerRS in E. coli, as suggested by biochemical studies (16,27,35).…”
Section: Resultssupporting
confidence: 53%
“…Small differences in interaction of the mutant enzyme with the various isoacceptors would have gone undetected, but there seems to be no discrimination against a particular tRNA species by the mutant enzyme. The finding of the LeuRS and SerRS mutants provides genetic evidence for the existence of a single LeuRS and SerRS in E. coli, as suggested by biochemical studies (16,27,35).…”
Section: Resultssupporting
confidence: 53%
“…This general notion was specifically contradicted by evidence on suppressor tRNA (3) and the fact that tRNAs with seemingly unrelated codons (e.g., serine) are recognized by one enzyme (4). Studies onmodification of tRNA by UV irradiation led to the proposal that the three last base-pairs in the amino-acid acceptor stem are the specific recognition site (5).…”
mentioning
confidence: 88%
“…It has been shown that separate tRNA 's pecies, one responding to codons UCA and UCG and the other to AGU and AGC, compete for synthetase and are thus recognizable to the same seryl-tRNA synthetase (277). This presents some peculiar problems, particularly in the case o~ tRNÃ ot, which has codons UCU, UCC, UCA, UCG, and AGU and AGC.…”
Section: Am~noacyl-trna Syntitetasesmentioning
confidence: 99%